The Ascetic Tradition and the English College at Valladolid - Williams, Michael E. (Studies in church history, 1985)
The history of English Roman Catholicism from the end of the sixteenth century right through to the nineteenth has as one of its main features the rivalries between seculars and regulars, especially between the seculars and the Jesuits. As this dispute primarily, but not exclusively, concerns the clergy it is most clearly seen in the history of those colleges which provided clergy for the English mission. The early history of the English College in Rome is not only the story of English and Welsh rivalry, but of frequent objections to the Jesuit administration and accusations by the seculars of the enticement of students to join the Society. Similar cases are to be found in the history of Saint Alban’s College Valladolid, but in this college there is an added dimension. Not only did the seculars complain about the Jesuits but the Jesuits complained of students being enticed away to the Benedictines. Later, a certain amount of bitterness arose out of the establishment of a college directed by the seculars in Lisbon. The Jesuits considered that they should have been placed in charge. What is more, there were even quarrels among the catholics detained in Wisbech castle. The ‘stirs’ there bore a remarkable resemblance to those at the college in Rome. As Aveling remarks about English Roman Catholicism ‘Historians have been defeated by its immense complexities of ecclesiastical intrigue and embarrassed by its sheer ferocity’. The quarrels not only provoke a feeling of distaste in the modern mind — why couldn’t these people resolve their differences and get on with their spiritual mission? They also instil puzzlement - are these disputes to be explained solely as political intrigue and in-fighting within the Catholic party? If so, how could such a cause appear attractive or plausible? How could such a house divided against itself, stand? I want to suggest that there is an element often overlooked which, although not explaining fully these intrigues and dissensions, nevertheless might help us to understand better what was going on. This can be called the positive attraction of the ascetic ideal. Bossy has stated in reference to the history of the English Catholic community ‘martyrology pointed this subject historiographically speaking up a cul-de-sac’. I want to suggest that cul-de-sac or no, the consideration of martyrdom and of life as a preparation for martyrdom is a path that can lead to a vantage point from which one can view this clerical back biting and contentiousness in a clearer light. Evenett in his Birbeck Lectures in 1951 pleaded for a better integration of the history of spirituality into ecclesiastical history and in particular devoted some space to a consideration of the origins of the Catholic revival in Spain. He pointed out the overlap of those who abandoned the world with those who remained in it, reforming its practice. Speaking of the Carthusians of the sixteenth century he said ‘A larger interest and practical usefulness in the external affairs of the Church were manifest by them at this period than we are accustomed to associate with modern Parkminster or Miraflores’. Following these lines let us turn to certain aspects of Spanish spirituality and its relationship to England.